Rapid deposition of superhydrophilic stalagmite-like protrusions for underwater selective superwettability. Issue 92 (19th September 2016) - Yang, Ching-Yu; Lo, Yu-Hsiang; Liu, Chang; Cheng, Hsin-Ming; Duh, Jenq-Gong; Chen, Po-Yu
Abstract : Hierarchically stalagmite-like tungsten-oxide protrusions on stainless steel mesh exhibited superior selective superwettability toward low surface tension oils under harsh environments. Abstract : Selective superwettability has attracted much attention for various applications, especially for fabricating membranes for oil-water separation. However, most approaches were conducted using complicated chemical reactions or processes. In the present study, we developed a facile one-step method to coat hierarchically stalagmite-like protrusions on stainless steel mesh which was repellent to not only oil, but various organic solvents underwater. The modified stainless steel mesh, prepared using an atmospheric pressure plasma technique, showed superhydrophilicity without any further surface elaboration. Due to its strong affinity toward water molecules, it enables the stable entrapment of a water layer on the surfaces of mesh wires against oils. High underwater static contact angles and extremely low roll-off angles towards various oil were exhibited. Notably, the selective superwettability was well preserved even under harsh environments, such as saline water and strong acid solution. Satisfactory separation efficiency for oil-water mixtures was demonstrated in this study. Furthermore, the effect of surface roughness in terms of intrusion pressure was investigated. The effect of surface roughness on intrusion pressure presented here can be applied for various coating materials used in oil-water separation.